The influence of the tourism sector on economic growth and labor absorption in the province of bali - Hutama, Dhiki Ardin; Suliswanto, Muhammad Sri Wahyudi (Universitas Pendidikan Indonesia, 2023)
ABSTRACTCurrently, many countries are discussing the possibility of recession and depression in their respective countries. Including Indonesia. The purpose of this study is to determine the influence of the variable Number of Tourist Visits on Economic Growth, to know the influence of the variable Number of Hospitality Accommodations on Economic Growth, to know the influence of the variable Number of Tourist Visits on Labor Absorption, to know the effect of the variable Number of Hospitality Accommodations on Labor Absorption, to know the influence of the variable Economic Growth on Labor Absorption, Type The research methodology is quantitative. Quantitative research involved the use of numerical data in the form of numbers or statements that are assessed and analyzed by statistical analysis. Quantitative data consists of the number of tourist visits, the number of hotel accommodations, the economic growth of Bali Province, and the labor absorption of Bali Province. Quantitative research is research that uses data in the form of numbers or statements that are assessed and analyzed by statistical analysis. The number of accommodation businesses has a positive influence on economic growth. Together the independent variables affect economic growth in Bali. Partially independent variables of tourist visits do not have a significant influence on labor absorption in Bali.ABSTRAKSaat ini banyak negara memperbicangkan kemungkinan terjadi resesi dan depresi di negaranya masing-masing. Mengetahui termasuk diantaranya. Tujuan penelitian ini Untuk mengetahui pengaruh variabel Jumlah Kunjungan Wisatawan terhadap Pertumbuhan Ekonomi, Untuk mengetahui pengaruh variabel Jumlah Akomodasi Perhotelan terhadap Pertumbuhan Ekonomi, Untuk mengetahui pengaruh variabel Jumlah Kunjungan Wisatawan terhadap Penyerapan Tenaga Kerja, Untuk mengetahui pengaruh variabel Jumlah Akomodasi Perhotelan terhadap Penyerapan Tenaga Kerja, Untuk mengetahui pengaruh variabel Pertumbuhan Ekonomi terhadap Penyerapan Tenaga Kerja, Jenis penelitian yang digunakan adalah penelitian ini ialah kuantitatif. Penelitian kuantitatif yaitu penelitian yang menggunakan data berupa angka atau pernyataan yang dinilai dan dianalisis dengan analisis statistik. Data kuantitatif terdiri dari Jumlah Kunjungan Wisatawan, jumlah akomodasi perhotelan Pertumbuhan Ekonomi Provinsi Bali dan Penyerapan Tenaga Kerja Provinsi Bali. Penelitian kuantitatif adalah penelitian yang menggunakan data berupa angka atau pernyataan yang dinilai dan dianalisis dengan analisis statistik. Jumlah usaha akomodasi memberikan pengaruh positif terhadap pertumbuhan ekonomi. Secara bersama-sama variabel indenden mempengaruhi pertumbuhan Ekonomi di Bali. Secara Parsial variabel independen kunjungan wisatawan tidak memberikan pengaruh secara signifikan terhadap penyerapan tenaga kerja di Bali.